The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.4187/respcare.06079
|View full text |Cite
|
Sign up to set email alerts
|

Heliox Adjunct Therapy for Neonates With Congenital Diaphragmatic Hernia

Abstract: The addition of heliox to the standard practice of permissive hypercapnia facilitated improvement in gas exchange, which allowed a decrease in ventilator settings and oxygen exposure, both of which are known to contribute to lung injury in this population. A prospective trial is needed to more clearly define the acute and long-term impacts of this treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Utilising heliox as an adjunctive therapy to the ventilation of infants with CDH was shown in one retrospective cohort study to be beneficial in reducing levels of hypercapnia (68 vs. 49 mmHg; p < 0.001) and levels of maximal ventilatory support required from high frequency oscillatory ventilation, and thus may be one such therapy to improve gas exchange in those with lung hypoplasia (57). Prospective randomised trials are required to ascertain the benefit of such therapy on short-and long-term pulmonary outcomes.…”
Section: Heliox Therapymentioning
confidence: 99%
“…Utilising heliox as an adjunctive therapy to the ventilation of infants with CDH was shown in one retrospective cohort study to be beneficial in reducing levels of hypercapnia (68 vs. 49 mmHg; p < 0.001) and levels of maximal ventilatory support required from high frequency oscillatory ventilation, and thus may be one such therapy to improve gas exchange in those with lung hypoplasia (57). Prospective randomised trials are required to ascertain the benefit of such therapy on short-and long-term pulmonary outcomes.…”
Section: Heliox Therapymentioning
confidence: 99%
“…Chest X-ray after 5 h of Heliox MV revealed decreased air-trapping; significant improvement of oxygenation was also observed ( 14 ). Concurrent use of Heliox and iNO was also reported in infants with congenital diaphragmatic hernia ( 32 ).…”
Section: Clinical Applications Of Helioxmentioning
confidence: 90%
“…Analysis of available data suggests that in infants Heliox should be administered with positive pressure in order to observe its beneficial effects. Its application was combined with HFNC, nCPAP, NIPPV, NIV-NAVA and in the intubated neonates ( 11 , 14 , 32 , 54 ). Conventional ventilation with Heliox requires a variable orifice proximal flow sensor as standard hot-wire sensors will not provide reliable measurements ( Figure 4 ).…”
Section: Practical Issuesmentioning
confidence: 99%
“…Originally, HFOV is a ventilatory method that uses a high lung expansion pressure and tidal volume below the anatomical dead space to maintain lung oxygenation (open lung approach) and to decrease ventilator-induced lung injury. Therefore, the main indications for HFOV would be diseases presenting with low lung compliance and hypoxia such as pneumonia, adult respiratory distress syndrome, and congenital diaphragmatic hernias (7). Contrastingly, diseases with increased airway resistance-such as bronchial asthma, bronchiolitis or tracheal stenosis-are more problematic since they result in signi cant hypercapnia compared with hypoxemia.…”
Section: Discussionmentioning
confidence: 99%
“…Helium-oxygen gas mixtures have been used in several clinical scenarios, such as bronchiolitis and other forms of distal airway obstruction, as it is known to signi cantly decreasing airway resistance and ease breathing(6). In addition, a recent retrospective cohort study showed that a helium-oxygen gas mixture improved CO 2 washout in conventional mechanical ventilation (CMV) and decreased settings of ventilator in neonates with congenital diaphragmatic hernias (7).…”
Section: Introductionmentioning
confidence: 99%